"Y"-shaped BP/PbS/PbSe nano-devices based on silicon carbide nanoribbons. Issue 61 (12th October 2018) - Zhang, Lishu; Li, Tao; Jiang, Yangyan; Arandiyan, Hamidreza; Li, Hui
Abstract : Quantum mechanics-based simulations have been undertaken to support the development and application of multi-functional nano-devices constructed from zigzag silicon carbide nanoribbons, boron phosphide, nanoribbons, and Pb-chalcogenide (PbS, PbSe) nanoribbons. Abstract : Quantum mechanics-based simulations have been undertaken to support the development and application of multi-functional nano-devices constructed from zigzag silicon carbide nanoribbons (zSiCNRs), boron phosphide (BP), nanoribbons (zBPNRs), and Pb-chalcogenide (PbS, PbSe) nanoribbons. We explore the effect of gate voltage on the electronic performance of the devices. Symmetric I – V characteristics, spin polarization properties, NDR effects, and high rectification ratios are observed among these devices. The effects of the angle, length and width of the constructed nanoribbon are also studied. The results show that the width of the nanoribbons can have a substantial influence on their electronic performance. These results provide a crucial simulation input to help guide the design of multi-functional nano-devices built from hybrid SiC–BP/PbS/PbSe nanostructures, and this research is essential for better understanding of their electronic transport properties.